2021
DOI: 10.1186/s12862-021-01935-1
|View full text |Cite
|
Sign up to set email alerts
|

Divergence time estimation of Galliformes based on the best gene shopping scheme of ultraconserved elements

Abstract: Background Divergence time estimation is fundamental to understanding many aspects of the evolution of organisms, such as character evolution, diversification, and biogeography. With the development of sequence technology, improved analytical methods, and knowledge of fossils for calibration, it is possible to obtain robust molecular dating results. However, while phylogenomic datasets show great promise in phylogenetic estimation, the best ways to leverage the large amounts of data for diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 90 publications
(147 reference statements)
6
19
0
Order By: Relevance
“…Moreover, the estimated divergence time between peafowl and turkey was near the divergence time among chicken and the ancestors of peafowl and turkey, and belonged to the Tertiary era. We speculated that the number of species and outgroup or dataset have an effect on phylogeny and divergence time [ 105 ]. Notably, we observed that FOXP3 and TP53 were mainly species-specific genes of peafowl compared to other Phasianidae.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the estimated divergence time between peafowl and turkey was near the divergence time among chicken and the ancestors of peafowl and turkey, and belonged to the Tertiary era. We speculated that the number of species and outgroup or dataset have an effect on phylogeny and divergence time [ 105 ]. Notably, we observed that FOXP3 and TP53 were mainly species-specific genes of peafowl compared to other Phasianidae.…”
Section: Discussionmentioning
confidence: 99%
“…To generate a reduced dataset that was more computationally tractable, we performed both gene and sample selection. Eighty‐six genes were chosen from the 429 individual gene alignments (~1/5 of the total genes) filtering first to obtain tree‐like loci, then filtering for the most clock‐like loci and finally filtering for tree length using SortaDate (Chen et al, 2021; Smith et al, 2018). We then selected 107 samples (~1/7 of the total samples) to represent all the tribes and major lineages with a preference of those with less missing data (missing nucleotides <20% in the 86‐gene dataset).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the limitation of calibration sources, the choice of molecular technique can improve divergence time estimation; genomes, transcriptomes, and targeted enrichment methods provide hundreds or thousands of loci among which it is possible to choose the most suitable ones (clock-like or tree-like [49]).…”
Section: Advancesmentioning
confidence: 99%